Effect of Gelatin-Based Edible Coatings Incorporated with Aloe vera and Black and Green Tea Extracts on the Shelf Life of Fresh-Cut Oranges - Mohsen Radi; Elham Firouzi; Hamidreza Akhavan; Sedigheh Amiri (Journal of Food Quality)
The aim of this study was to evaluate the effect of gelatin coating incorporated with Aloe vera gel (50,100%) and green and black tea extracts (5,10%) on physicochemical, microbial, and sensorial properties of fresh-cut oranges at 4°C for 17 days. Significant differences in terms of quality parameters were observed between the control and coated fresh-cut oranges. The highest variation of quality parameters was observed in control, while the least variations were observed in coated slices with 100% Aloe vera and 10% green tea extract. The weight loss was increased with time, but the coating treatment especially with 100% Aloe vera had significant effect on the prevention of weight loss. Also, Aloe vera coated samples obtained the highest score in sensory evaluation. Coating with gelatin incorporated with Aloe vera and green tea extracts successfully retarded the microbial growth and therefore extended the shelf life of fresh-cut oranges during cold storage.